2015
DOI: 10.1016/j.joca.2015.02.515
|View full text |Cite
|
Sign up to set email alerts
|

Vastus medialis fat infiltration – A modifiable determinant of knee cartilage loss

Abstract: Purpose: Although obesity is a risk factor for hip osteoarthritis (OA), the role of body composition, if any, is unclear. This study examines whether obesity and body composition are associated with hip cartilage changes using magnetic resonance imaging (MRI) in community-based adults. Methods: 141 community-based participants with no clinical hip disease, including OA, had BMI and body composition (fat mass and fat free mass) measured at baseline (1990 to 1994), and BMI measured and 3.0T MRI performed at foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Higher quadriceps intra-muscular adipose tissue was associated with advanced age, worse K-L score, and greater cartilage and meniscus lesions, and also predicted selfreported disability 12 . Teichtahl et al investigated the association between intra-muscular adipose tissue infiltration in vastus medialis (VM), a functionally important quadriceps muscle, and knee cartilage volume, and reported that reduced VM adipose tissue infiltration could predict the reduction of annual loss of cartilage volume in both medial tibial and patellar sites 27 . They also examined the determinants of VM adipose tissue infiltration and reported that age, female gender, BMI and weight had positive, while physical activity had negative, associations with baseline VM adipose tissue infiltration.…”
Section: Intra-and Inter-muscular Adipose Tissuementioning
confidence: 99%
“…Higher quadriceps intra-muscular adipose tissue was associated with advanced age, worse K-L score, and greater cartilage and meniscus lesions, and also predicted selfreported disability 12 . Teichtahl et al investigated the association between intra-muscular adipose tissue infiltration in vastus medialis (VM), a functionally important quadriceps muscle, and knee cartilage volume, and reported that reduced VM adipose tissue infiltration could predict the reduction of annual loss of cartilage volume in both medial tibial and patellar sites 27 . They also examined the determinants of VM adipose tissue infiltration and reported that age, female gender, BMI and weight had positive, while physical activity had negative, associations with baseline VM adipose tissue infiltration.…”
Section: Intra-and Inter-muscular Adipose Tissuementioning
confidence: 99%
“…Intramuscular quadriceps adiposity is increasingly being recognized as an important component of knee osteoarthritis (OA) pathogenesis (1)(2)(3). The mechanisms are likely related to release of inflammatory cytokines from the adipose tissue and their effects on the knee joint, as well as the effects of muscle adiposity on muscle function (4).…”
Section: Introductionmentioning
confidence: 99%
“…To verify or dispute hypothetical evidence based associations depicted in Figure 1 and expand upon trends depicted in Table 2, more prospective studies focusing on muscle co-activation effects [17], the role of eccentric as well as concentric forces on the emergence and progression of osteoarthritic joint disease [40], as well as the role of distant muscles [42,69], and the tendon-aponeurosis complex [46] are indicated [46,59]. In addition, delineating the role of muscle fat infiltration [33,81], muscle inflammation [25], and vitamin D [30] and its impact on muscle structure and function in the context of osteoarthritis may…”
Section: Implications and Conclusionmentioning
confidence: 94%